CCBC Choices 2011 - Schliesman, Megan; Lindgren, Merri V.; Horning, Kathleen T. (My University, 2011)
CCBC CHOICES is an annual list of recommended books for children and young adults selected by the librarians at the Cooperative Children's Book Center, a library of the School of Education at the University of Wisconsin-Madison. CCBC CHOICES 2011 recommends 240 titles for children and young adults published in 2010. It includes a commentary on the 2010 publishing year, including statistics on the number of books by and about people of color published for children and teens.
Carling Febry contributed to this publication.
Keywords: multicultural literature; young adult literature; children's literature